Gate-induced drain leakage current characteristics of p-type polycrystalline silicon thin film transistors aged by off-state stress. (October 2018) - Park, J.; Jang, K.S.; Shin, D.G.; Shin, M.; Yi, J.S.
Highlights: Off-state bias stress is investigated for p-type poly-Si TFTs. Experimental and quantitative study is performed for off-state stress effects. GIDL current of poly-Si TFT can be successfully reduced by off-state bias stress. TCAD simulations are performed to understand the mechanisms of off-state bias stress. Local defect creation and charge trapping are key factors of GIDL current reduction. Abstract: Thin film transistors have become crucial components of several electronic display devices. However, high leakage current is a frustrating impediment to increasing the efficiency of these transistors. We have performed an experimental and quantitative study on the effects of off-state bias stress on the characteristics of a p-type polycrystalline silicon (poly-Si) thin film transistor (TFT). The gate-induced drain leakage (GIDL) current under off-state bias stress conditions was investigated by changing gate-source voltage ( V gs ) and drain-source voltage ( Vds ). Off-state bias stress was found to dramatically increase the threshold V gs from 1 to 11 V, thereby increasing the voltage needed to turn off the TFT, without causing significant changes in on-state current or subthreshold swing. We developed local defect creation and charge trapping models for a technology computer-aided design simulation platform to understand the mechanisms underlying these observed effects. Using the model, we showed that off-state stress induces charge trapping within the local defects of a high electric field region in the TFT channel near the drain. This reduces the electric field and thermionic field-emission current, which in turn lowers the GIDL current by increasing threshold voltage V gs .